Three-Dimensional (3D) Reconstruction for Detecting Shape and Volume of Lung Cancer Nodules - Rodiah Rodiah; Sarifuddin Madenda; Fitrianingsih Fitrianingsih (Institut Teknologi Sepuluh Nopember, 2014)
The development of CT scanning technology as a digital image recorder has provided facilities for oncologists in analyzing the presence of cancer in patient's organs. Visually, oncologists analyze it by looking at the CT slices to ascertain whether any cancer nodules in the lung are present. The center line of nodules is used to calculate the volume of nodules for all slices. Volume is used to monitor the rate of cancer growth. Another way is the shape of cancer nodules. However, since the CT scan images are in the form of two-dimensional (2D), it is hard for oncologists to see the full three-dimensional (3D) shape of the cancer nodules. Based on that matter, this study aimed to develop algorithm that can automatically detect and calculate volume of nodules for all slices in 3D reconstruction. 3D reconstruction of cancer nodules is performed through linear interpolation approach. The results of the developed algorithm, tested through a number of slice images from lung CT scan, showed that the approach and algorithm are able to reconstruct nodule shape in 3D and calculate volume automatically. The results obtained are expected to be able to help oncologists provide accurate information of cancer nodules as well as volume and shape of the cancer nodules in 3D surface.